Life Cycle Assessment Approach on Food Packaging to Build Sustainable Consumption Awareness in Developing Countries - NiLuh Widyaningsih (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
Household consumption is the value of products bought by the household. Consumption takes the biggest part in our lives to support our basic needs on food, clothe, and shelter. The products packaging do not come from natural anymore but from the man-made, such as paper, plastic, glass or metal. Most of the packaging become waste into the environment. There are organic and inorganic waste. The increasing number of population will increase the demand on the products and it will create more waste. Indonesia is the 4th most populated country in the world and it has still waste management problems in urban and rural area. In 2014 from my research, Jakarta has higher percentage on non-food than on food consumption but the contribution from food products into the local economy gets higher every year. We can see this phenomena almost in every place. This research used qualitative approach to gather data and information regarding people’s perception about household solid waste from their consumption behavior. The data do not available on the lower level adminitration. From the focus group discussion in Setia Asih Village (Bekasi) showed that local people and government have less knowledge on household solid waste, especially the life cycle via food packaging and how to treat the waste. So, I build a concept to solve the mind-set issue on the sustainable consumption awareness through the life cycle assessment approach. Local people and government can used it to improve their quality of life (social and economy) and environmental condition.